The Influence of Pre-Training Factors on Training Effectiveness Mediated by Motivation to Learn, Motivation to Transfer, and Self-Efficacy – Case Study on Non-Ministerial Government Institutions - Kristianto Saputro; Muhammad Irfan Syaebani (Quantitative Economics and Management Studies, 2024)
While acknowledging the importance of training, the challenge lies in understanding and optimizing its effectiveness, especially in the context of the government institution’s ever-changing landscape and the associated budgetary considerations. It examines whether pre-training factors—organizational support, training environment, trainer quality, and training need analysis— influence training effectiveness directly or are mediated by motivation to learn, motivation to transfer, and self-efficacy in non-ministerial government institutions in Indonesia. Data were collected from 202 respondents across 19 institutions using purposive sampling and analyzed with Covariance Based-Structural Equation Modeling (CB-SEM) using Lisrel 8.80. The findings reveal that trainer quality significantly affects motivation to learn, motivation to transfer, and self-efficacy but does not directly impact training effectiveness. Instead, its influence is mediated by motivation to transfer and self-efficacy. This underscores the crucial role of trainers in enhancing training effectiveness by boosting participants' motivation and self-efficacy. The study highlights the need for organizations to invest in high-quality trainers through ongoing professional development, robust evaluation systems, and incentives to improve training outcomes and achieve organizational goals more efficiently.